2017
DOI: 10.1038/srep44845
|View full text |Cite
|
Sign up to set email alerts
|

Odd Chain Fatty Acids; New Insights of the Relationship Between the Gut Microbiota, Dietary Intake, Biosynthesis and Glucose Intolerance

Abstract: Recent findings have shown an inverse association between circulating C15:0/C17:0 fatty acids with disease risk, therefore, their origin needs to be determined to understanding their role in these pathologies. Through combinations of both animal and human intervention studies, we comprehensively investigated all possible contributions of these fatty acids from the gut-microbiota, the diet, and novel endogenous biosynthesis. Investigations included an intestinal germ-free study and a C15:0/C17:0 diet dose respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
95
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 30 publications
12
95
0
2
Order By: Relevance
“…In conclusion, blood C15:0 levels showed strong evidence of reproducibility over time and sensitivity to change in intake of high-fat dairy products, comparable to the values found for the well-established biomarker EPA+DHA for oily fish intake, which are important conditions for the usefulness of biomarkers in the study of dietary intakes and nutrientdisease relationships. Results for C17:0 question its role as a dietary biomarker and supports recent research demonstrating substantial biosynthesis of C17:0 [26,29]. This taken together with our previous results supports C15:0 only as a biomarker of dairy intake [3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, blood C15:0 levels showed strong evidence of reproducibility over time and sensitivity to change in intake of high-fat dairy products, comparable to the values found for the well-established biomarker EPA+DHA for oily fish intake, which are important conditions for the usefulness of biomarkers in the study of dietary intakes and nutrientdisease relationships. Results for C17:0 question its role as a dietary biomarker and supports recent research demonstrating substantial biosynthesis of C17:0 [26,29]. This taken together with our previous results supports C15:0 only as a biomarker of dairy intake [3].…”
Section: Discussionsupporting
confidence: 90%
“…The existence of such pathways has been postulated on the basis of the higher levels of C17:0 observed in different lipid fractions in humans compared to what would be expected from the ratio of these fatty acids in milk fat . More recently strong evidence has emerged that supports the endogenous biosynthesis of C17:0 . This biosynthesis of C17:0 could explain higher mean levels of heptadecanoic acid in the current data and the lower ICCs.…”
Section: Discussionmentioning
confidence: 52%
“…S2). Furthermore, we also showed higher abundances of PC metabolites containing C18 : 0 moieties during the MCTD phase, further allowing the potential for α-oxidative biosynthesis of C17 : 0 from C18 : 0 moieties, as suggested by Jenkins et al (37) . Detection of C17 : 0 moieties in lipid metabolites is particularly interesting when considering the neuroprotective properties of triheptanoin, a TAG consisting of three heptanoate (C7 : 0) FA, especially as C17 : 0 fatty acyl moieties can be metabolised to C7 : 0 moieties after five cycles of β-oxidation (online Supplementary Fig.…”
supporting
confidence: 79%
“…In lipid metabolism, α-oxidation refers to a metabolic process that results in the removal of a single carbon unit from a fatty acyl chain, whereas β-oxidation refers to the metabolic removal of two carbon units. Jenkins et al (37) showed that phytanic acid, a substrate for α-oxidation, significantly decreased C17 : 0 biosynthesis by competitive inhibition, further suggesting that C17 : 0 is biosynthesised by α-oxidation. Here we present data showing significant increases in C17 : 0 moieties during the MCTD phase when compared with the placebo, where the only difference between the diet phases was the presence or absence of medium-chain (C8, C10 and C12) fatty acyl moieties.…”
mentioning
confidence: 99%
“…Selv om konsentrasjonene av disse fettsyrene korrelerer med inntak av meieriprodukter, korrelerer de også med alt fra fisk til grønnsaker. Det ser også ut til at de i en viss grad kan syntetiseres bakterielt i tarmen 241 , spesielt C17:0 (som er den fettsyren som i størst grad er knyttet til lavere risiko for sykdom) 242 . Forholdet mellom C15:0 og C17:0 i melkefett er rundt 2:1, men rundt 1:2 i blodet 243 .…”
Section: Biomarkører På Fettinntakunclassified